Pengembangan Media Pembelajaran Video Animasi Berbasis Aplikasi Inshot Pada Tema 5 Kelas II SDN 040556 Juhar - Yemima Anastasya Br Ginting; Robenhart Tamba (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the feasibility, practicality and effectiveness of InShot application-based animated video learning media on theme 5 class II SDN 040556 Juhar. This type of research is a type of development research (Research and Development) using the 4D (Four D) development model. The instruments used are media expert validation sheets, material experts, educational practitioner assessments, student responses and tests (pre-test and post-test). The results of research related to feasibility show that the results of media expert validation fall into the